A spectral perspective on excess volatility - Giacomo Livan; Simone Alfarano; Mishael Milakovic; Enrico Scalas (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
We perform a careful spectral analysis of the correlation structures observed in real and financial returns for a large pool of long-lived US corporations, and find that financial returns are characterized by strong collective fluctuations that are absent from real returns. Once the excessive comomvement is subtracted from individual financial time series, the behavior of real and financial returns is virtually identical in both the cross-sectional and time series domains, thereby demonstrating the inherently collective nature of excessive fluctuations. Put differently, if excess volatility is to be reduced then one would do well to inhibit excess comovement first. At any rate, the excessive behavior in volatility and comovement should no longer be studied in isolation of each other.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330